Role of Solar Photovoltaic Energy in GHG Emission Reduction within Indonesia’s Long-Term Strategy for Low Carbon and Climate Resilience 2050 - Tarigan, Elieser (International Journal of Energy Economics and Policy, 2025)
Indonesia’s Long-Term Strategy for Low Carbon and Climate Resilience 2050 (LTS-LCCR 2050) outlines ambitious goals for achieving a low- carbon and climate-resilient future, with solar photovoltaic (PV) energy playing a pivotal role. This paper explores the pathways, contributions, and challenges associated with achieving the target of 113 GW of installed solar PV capacity by 2050. Using a comprehensive methodology, the study examines solar energy potential, trends in PV deployment, greenhouse gas (GHG) emission reductions, and scenarios for target achievement. Findings highlight that transitioning to solar PV could reduce GHG emissions by approximately 794.87 million tons of CO2 annually by replacing coal-based electricity. Three deployment scenarios are analyzed: constant growth, gradual ramp-up, and aggressive early deployment, each presenting unique challenges and opportunities. Key barriers include financial constraints, technical limitations, regulatory hurdles, and public acceptance issues. The study concludes that achieving the target requires strong policy frameworks, significant investments, and technological innovation. Solar PV has the potential to transform Indonesia’s energy sector, contributing to national climate goals and sustainable development.